Outcomes of Teletherapy and Face-to-Face Voice Therapy for Vocal Fold Nodules: A First-Line Treatment Comparison - Altan, Esma; Barmak, Elife; Yılmaz, Zeynep; Söylemez, Dilara; Pütürgeli Özer, Tuğçe; Çadallı Tatar, Emel (The European Research Journal, 2026)
Objectives: This study aimed to compare the effectiveness of teletherapy and face-to-face voice therapy in patients diagnosed with vocal fold nodules by evaluating acoustic, aerodynamic, perceptual, and patient-reported voice outcomes. Methods: A total of 40 patients with vocal fold nodules received either teletherapy or face-to-face voice therapy for a period of six to eight weeks. Voice assessments were performed before and after therapy and included videolaryngoscopic examination, acoustic voice analysis, aerodynamic voice measurements, auditory-perceptual voice evaluation, and patient-reported outcome measures related to voice handicap, voice-related quality of life, and reflux-related symptoms. Results: Both therapy groups demonstrated significant improvements in acoustic voice stability, perceptual voice quality, and patient-reported voice outcomes after treatment. No significant differences were observed between teletherapy and face-to-face therapy for most outcome measures. Patients receiving face-to-face therapy showed a greater change in fundamental frequency compared with those receiving teletherapy. Both therapy modalities were associated with significant reductions in voice-related handicap, improvements in voice-related quality of life, and decreased reflux-related symptoms. Conclusions: Teletherapy appears to be an effective and accessible alternative to face-to-face voice therapy for patients with vocal fold nodules. Further studies are warranted to investigate long-term outcomes and to explore integrated and hybrid treatment models in voice rehabilitation.